Verbal instructions as selection bias that modulates visual selection - Damanskyy, Yevhen (Visual cognition, 2023)
Research has shown that in addition to top-down and bottom-up processes, biases produced by the repetition priming effect and reward play a major role in visual selection. Action control research argues that bidirectional effect-response associations underlie the repetition priming effect and that such associations are also achievable through verbal instructions. This study evaluated whether verbally induced effect-response instructions bias visual selective attention in a visual search task in which these instructions were irrelevant. In two online experiments (Exp.1, N = 100; Exp. 2, N = 100), participants memorized specific verbal instructions before completing speeded visual-search classification tasks. In critical trials of the visual search task, a priming stimulus specified in the verbal instructions matched the target stimulus (positive priming). In addition, the design of Experiment 2 accounted for the repetition priming effect caused by frequent appearance of the target object. Reaction time analysis showed that verbal instructions inhibited visual search. Response error analysis showed that verbal effect-response formed an effect-response association between verbally specified stimulus and response. The results also showed that the target object's frequent appearance strongly affected visual search. The overall findings showed that verbal instructions extended the list of selection biases that modulate visual selective attention.